State of the world, 1997 : a Worldwatch Institute report on progress toward a sustainable society - Brown, Lester R. 1934-; Worldwatch Institute (New York : Norton, 1997)
"Presents evidence of the birth of an entirely new economy, an environmental revolution that may be as sweeping as the Industrial Revolution that put us on our present unsustainable course. The authors argue that, far from being too costly to consider, the transition to an environmentally sustainable economy represents the greatest investment opportunity in history."--Back cover.
A new economy for a new century / Lester R. Brown and Christopher Flavin -- Reinventing the energy system / Christopher Flavin and Seth Dunn -- Forging a sustainable materials economy / Gary Gardner and Payal Sampat -- Reorienting the forest products economy / Janet N. Abramovitz and Ashley T. Mattoon -- Charting a new course for oceans / Anne Platt McGinn -- Appreciating the benefits of plant biodiversity / John Tuxill -- Feeding nine billion / Lester R. Brown -- Exploring a new vision for cities / Molly O'Meara -- Ending violent conflict / Michael Renner -- Building a sustainable society / David Malin Roodman.
Includes bibliographical references (p. [189]-248 and index.
Keywords: Economic history -- 1990-; Sustainable development; Environmental policy; Desarrollo sostenible; Política ambiental